Evidence of Failure of Oral Third-Generation Cephalosporin Treatment for Shigella sonnei Infection. (18th April 2020) - Collins, Jennifer P; Friedman, Cindy R; Birhane, Meseret G; Karp, Beth E; Osinski, Anthony; Montgomery, Mary W; Thomas, Deepam; Barkley, Jonathan; Sanchez, Martha C; Hanna, Samir; Adediran, Azizat A; Chen, Jessica C; et al.
Abstract: In 2017, state health departments notified the Centers for Disease Control and Prevention about 4 patients with shigellosis who experienced persistent illness after treatment with oral third-generation cephalosporins. Given increasing antibiotic resistance among Shigella, these cases highlight the need to evaluate the efficacy of oral cephalosporins for shigellosis.